A systematic literature review of the mechanisms linking crime and poverty - Gaitán-Rossi, Pablo; Velázquez Guadarrama, César (Convergencia Revista de Ciencias Sociales; Vol. 28 (2021)DO - 10.29101/crcs.v28i0.14685, 2021)
The objective was to identify the social mechanisms linking crime and poverty in urban settings to discuss whether crime should be included in multidimensional poverty measures. The method was a systematic literature review in which we examined 1,505 academic articles and selected fifty-nine for an in-depth analysis. A qualitative coding then helped to describe key findings. Results show most research focused on how poverty leads to crime, while few articles explored the inverse relation, which is the most needed for a poverty measure. The clearest expressions of urban poverty and crime were the concentration of disadvantages, the socioeconomic and spatial segregation, and low levels of collective efficacy. We conclude that the evidence of crime as a determinant of poverty in urban enclaves is insufficient due to key measurement challenges. However, the review shows several ways in which crime is a central aspect of the conditions and experience of poverty.